Ship- Source Marine Pollution, Legal Theory, Law and Practice: The Regime of Pakistan’s Perspective - Dar, Dr. Saira Bashir (Journal of Nautical Eye and Strategic Studies, 2025)
Ship-source pollution is a maritime menace which continues to harm the marine environment and also cause damage to persons and property, in particular, in the event of a serious oil spill. The international law governing such pollution is almost entirely contained in conventions addressing both the public as well as the private law dimensions of the subject. The principal purpose of this chapter is to address the private law side of the ship-source pollution equation focusing on a critical analysis of the legal regime in this field as it obtains in Pakistan, a common law jurisdiction. Pakistan is a party to the Civil Liability Convention, 1992 (CLC), but not to the Bunkers Convention of 2001. It is not as yet a party to the Fund Convention, 1992 but is looking to enter that convention. Pakistan is also not a party to the HNS Convention of 1996 modified by its 2010 Protocol. This chapter provides an overview of the legal theory of ship source marine pollution law from the perspective of both the private and public legal regimes in Pakistan. In conclusion, lacunae in the national law in both regimes are pointed out and commensurate proposals for their improvement and refinement are made.